2019
DOI: 10.1111/cas.14173
|View full text |Cite
|
Sign up to set email alerts
|

G9a and histone deacetylases are crucial for Snail2‐mediated E‐cadherin repression and metastasis in hepatocellular carcinoma

Abstract: Functional E‐cadherin loss, a hallmark of epithelial‐mesenchymal transition (EMT), is important for metastasis. However, the mechanism of Snail2 in hepatocellular carcinoma (HCC) EMT and metastasis remains unclear. Here, we showed that Snail2 was upregulated in primary HCC, and significantly increased during transforming growth factor‐β‐induced liver cell EMT. Snail2‐overexpressing and knockdown cell lines have been established to determine its function in EMT in HCC. H3K9 methylation was upregulated and H3K4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Acetylation of H3K4 and H3K56 within the Snail2 promoter was markedly reduced in EMT thanks to HDAC1 and HDAC3 [ 70 ]. It is worthy to note that G9a, a histone H3 lysine 9 (H3K9) methyltransferase, has been recently recognized as vital for such Snail2 -mediated inhibition of E-cadherin and consequent repression of mesenchymal properties [ 71 ]. It has even been targeted for therapy by administering its inhibitor, UNC0646, in nanodiamonds, which reduced H3K9 methylation and tumor invasiveness [ 72 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Acetylation of H3K4 and H3K56 within the Snail2 promoter was markedly reduced in EMT thanks to HDAC1 and HDAC3 [ 70 ]. It is worthy to note that G9a, a histone H3 lysine 9 (H3K9) methyltransferase, has been recently recognized as vital for such Snail2 -mediated inhibition of E-cadherin and consequent repression of mesenchymal properties [ 71 ]. It has even been targeted for therapy by administering its inhibitor, UNC0646, in nanodiamonds, which reduced H3K9 methylation and tumor invasiveness [ 72 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…The dysregulation of G9a and aberrant levels of H3K9me2 are involved in different types of human cancers [12][13][14][15] . As for HCC, G9a promotes tumor progression by silencing tumor suppressor genes or enhancing epithelial-mesenchymal transition 16,17 , and its inhibition reduces tumor aggressiveness 18,19 . In contrast, how G9a contributes to the development or initiation of HCC has not yet been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the expression of G9a is upregulated in a number of cancers, including aggressive lung cancer, multiple myeloma, aggressive ovarian carcinoma, brain cancer, hepatocellular carcinoma, esophageal squamous cell carcinoma, and malignant melanoma (Wozniak et al, 2007;Gao et al, 2013;Hua et al, 2014;Lehnertz et al, 2014;Hu et al, 2019;Dang et al, 2020). Higher G9a expression levels have often been associated with poor prognosis (Chen et al, 2010;Ke et al, 2014;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%